: Atención de enfermería en pacientes con complicaciones por enfermedad renal crónica avanzada - Fuertes Argoty, Francy Esmeralda (2022)
ABSTRACT: Advanced chronic kidney disease causes some complications which reduce the quality of life of the sufferer. Nursing and the explosion then become really important because of the identification, diagnosis, monitoring, preparation, and care that this population needs. Therefore, the goal of this study is to identify the nursing interventions required by patients who have complications from advanced chronic kidney disease. The method is a systematic, cross-sectional, qualitative-quantitative analysis of 312 documents consulted in primary information sources was carried out, using specialized search engines such as: Google Scholar, Scirus, SciELO, Redalyc, PubMed and Dialnet. Documents published in the period 2017-2022 in Spanish, English or Portuguese are included. In the case of being scientific articles they should be freely accessible, present a minimum of content on the subject of study and answer at least one of the following questions: What is advanced chronic kidney disease? What are the risk factors and complications of advanced chronic nephropathy? Which nursing procedures and care do ACKD patients need? patients on ACKD? As a result, ACKD goes unnoticed both by health professionals and by the affected individual himself, because this pathology is silent until prolonged stages and, in most cases, it is triggered secondary to other chronic degenerative diseases such as diabetes mellitus, arterial hypertension, metabolic syndrome, cardiovascular diseases or glomerulopathies. Aspects such as fall prevention, safety in the use of medications, hand hygiene and control of comorbidities become universal; Despite this, key interventions include regular follow-up, the inclusion of various professionals such as nutritionists, psychologists or community nurses, early preparation for the different renal replacement therapies, quality control of water and dialysis fluid, Membrane care or infection control should be considered necessary in any process and care plan in this population as needed. Finally, advanced chronic kidney disease is a public health problem worldwide; All health personnel, especially nursing, face a real challenge during the care of people with ACKD due to the complexity and possible complications that this pathology entails, therefore, work must be done to prevent, identify and treat it in a timely manner.